Reverberation Time Improvement in the Worship Room of Palihan Javanese Christian Church - Kartika Putri, Tabita Febriawaty; Setyowati, Erni (Journal of Architectural Research and Design Studies, 2023)
Acoustic comfort is one of four types of comforts in a room. Acoustic comfort allows users of worship spaces to be more focused and solemn in worshipping. One indicator that indicates the optimality of acoustic comfort is the level of clarity of sound articulation. The level of sound articulation in the worship space of the Palihan Javanese Christian Church is considered unclear, so it can be concluded if there is excessive reverberation time in the worship room. Therefore, it is necessary to improve the ideal reverberation time in the worship room of the Palihan Javanese Christian Church. The research was conducted using quantitative research methods. The improvement of reverberation time in this research is done by identifying the materials that are used in the worship room of the Palihan Javanese Christian Church at a frequency of 500Hz and 1000Hz using Sabine's reverberation time theory. From this research, it can be concluded that the replacement of some reflector materials with diffuser and absorber materials can reduce the excess reverberation time in the worship room of the Palihan Javanese Christian Church. Keywords: acoustic materials; improvement; reverberation time